PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN, MINAT BELAJAR, DAN LINGKUNGAN KELUARGA TERHADAP PRESTASI BELAJAR SEJARAH SISWA KELAS X DI MAN BALIKPAPAN - Nuorma Wahyuni (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2015)
In this issue, the researcher examines; (1) Is there any significant influence of using learning media to history learning achievement ? (2) Is there any significant influence of learning interest to history learning achievement? (3) Is there any significant influence of family environment to history learning achievement? (4) Is there any significant influence between using learning media, learning interest and family environment to history learning achievement ? There are 120 students, the researcher took 92 students. There are 3 variable that examines in this study ; learning media , learning interest , family environment and student learning achievement . This study is quantitative research, data collecting by using inquiry. Based on hypothesis test (1)Fcountis 2750 >Ftable270 mean Ho rejected proof the learning media has value 16,0 %. (2) )Fcountis 2719>Ftable270 mean Ho rejected proof learning interest has value 14,0 %. (3) Fcountis 2788>Ftable270 mean Ho rejected proof family environment has value 12,0 %. (4)Konstanta is 82.360 mean if learning media, learning interest and family environment has value 0. So student learning achievement has 0,027 increasing 0,087 to student learning achievement and family environment variable if the koefisien 0,063 so has increasing 0,063 to history learning achievement. The effective contribution of learning media, learning interest and family environment to history learning achievement is 42,0 %, it means that the influence of student achievement is more dominan in learning media 16,0 %, learning interest 14,0 % and family environment 12,0 %. The other factor has 58,0 % influence for this study.